2018
DOI: 10.1108/aeat-06-2016-0102
|View full text |Cite
|
Sign up to set email alerts
|

A simplified model for predicting the propeller-wing interaction

Abstract: Purpose The traditional numerical methods to predict the interaction between the wing and propeller are too complex and time-consuming for computation to a certain extent. Therefore, they are not applicable for a real-time integrated turboprop aircraft model. This paper aims to present a simplified model capable of high-precision and real-time computing. Design/methodology/approach A wing model based on the lifting line theory coupled with a propeller model based on the strip theory is used to predict the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Mieloszyk and Galinski (2013) have experimentally showed that the increase in lift of the UAV is not only caused by propeller in vertical direction, but it also depends upon some other factors such as flow on the wing. The aerodynamic characteristic of propeller-driven UAV is much depends on the propeller and wing flow interaction (Aref et al , 2018; Huang et al , 2018). The induced flow from the propeller has increased the free stream velocity above the wing and this situation will reduce the pressure distribution (Ahn and Lee, 2013; Chinwicharnam et al , 2015; Sudhakar et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mieloszyk and Galinski (2013) have experimentally showed that the increase in lift of the UAV is not only caused by propeller in vertical direction, but it also depends upon some other factors such as flow on the wing. The aerodynamic characteristic of propeller-driven UAV is much depends on the propeller and wing flow interaction (Aref et al , 2018; Huang et al , 2018). The induced flow from the propeller has increased the free stream velocity above the wing and this situation will reduce the pressure distribution (Ahn and Lee, 2013; Chinwicharnam et al , 2015; Sudhakar et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches based on potential methods and superposition of induced velocities but not using BEMT were tested, for exemple, by Chiocchia and Pignataro (1995), Fratello, Favier andMaresca (1991), andHuang, Zhao andHuang (2018), among other authors. In order to model distributed propulsion systems, Cole et al (2019) developed a high-order free-wake method for propeller-wing systems that was implemented using high-order vorticity elements distributed to represent the aircraft wing and the propeller blades.…”
Section: Methods For Aerodynamic and Aeroacoustic Modeling Of Install...mentioning
confidence: 99%